Assessing the Cost of Medical Intensive Care Unit at Tertiary Care Hospital in Delhi, India - Gadpayle, A. K.; Dangi, H. K.; Debopriya, . (Current Aspects in Business, Economics and Finance Vol. 3, 2022)
The study was conducted to assess the cost of per patient per day in Medical Intensive Care Unit (MICU). It is well known that the cost of critical care is expensive and also on increasing trend. This prospective study was conducted at tertiary care hospital, in Government setup, Delhi from 01st January 2014 to 31st January 2014. Various costs like fixed, variable, Direct and Indirect were calculate for the study period by step down approach. Throughout the study period, a total of 32 patients were admitted to the medical ICU. The average number of days for admissions was 171 days. The projected average stay time was 5.343 days. 42.44 percent of the overall cost is made up of the pay component. 37.00% of the overall cost is made up of the equipment costs. The combined fixed cost is 81.62 percent, while the combined variable cost is 18.38 percent. Radiology accounts for 6.35 percent of variable cost, followed by medicine (4.81 percent) and investigation (3.83 percent). A significant portion of the overall expenses in the medical ICU are fixed costs. which places equipment expense foremost. Given the close proximity of the ICU and the fact that patients admitted to the medical ICU are from outside, the unit cost of Rs. 1132.99/- is considerably lower than that found in other research.Keyword: Medical ICU, Unit cost.